INDONESIAN-ENGLISH CODE MIXING IN ANALISA'S YOUTUBE CHANNEL - Evi zulida; Fatma Zahara (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
This research aims to find out the levels and the factors of code mixing that appear on Analisa’s video YouTube channel. A qualitative method was used in this researchby employingadocument analysiswhich focused on analyzing the levels of code mixing defined by Suwito (1988) and the factors of code mixing argued by Suandi (2014). The data were collected from 5 session videos in Analisa’s video YouTube channel. Through data analysis, the results show that there are some levels of code mixing appear on Analisa’s video YouTube channel. They are word level, phrase level, clause level, baster level, and repetition word level. Then, there are some factors of code mixing appear on Analisa’s video YouTube channel. They are popular term factor, the speaker and speaker character factor, function and aim factor,main topic factor, and prestigious factor.It is hoped that the result of this study is useful to everyone who wants to conduct the study about code mixing.